Cross-sectional study on the weight and length of infants in the interior of the State of São Paulo, Brazil: associations with sociodemographic variables and breastfeeding - Bernardi, Julia Laura Delbue; Jordão, Regina Esteves; Filho, Antônio de Azevedo Barros (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Increasing obesity is starting to occur among Brazilians. The aim of this study was to investigate the weight and length of children under two years of age in relation to sociodemographic variables and according to whether they were breastfed. DESIGN AND SETTING: Cross-sectional randomized study conducted in 2004-2005, based on the declaration of live births (SINASC) in Campinas, Brazil. METHODS: 2,857 mothers of newborns were interviewed and answered a questionnaire seeking socioeconomic and breastfeeding information. The newborns’ weights and lengths were measured at the end of the interviews and the body mass index was calculated. Percentiles (< 15 and > 85) and Z-scores (< -1 and > +1) were used for classification based on the new growth charts recommended by WHO (2006). The log-rank test, multiple linear regression and binomial test (Z) were used. The statistical significance level used was 5%. RESULTS: The predominant social level was class C. The median for exclusive breastfeeding was 90 days; 61.25% of the children were between P15 and P85 for body mass index and 61.12% for length, respectively. Children whose mothers studied for nine to eleven years and children whose mothers were unemployed presented lower weight. Children whose mothers worked in health-related professions presented lower length when correlated with breastfeeding. CONCLUSION: The breastfeeding, maternal schooling and maternal occupation levels had an influence on nutrition status and indicated that obesity is occurring in early childhood among the infants living in the municipality.